2015
DOI: 10.1002/app.42751
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional ternary drug‐loaded electrospun scaffolds

Abstract: Multifunctional electrospun scaffolds were prepared from two PLA grades having slightly different D-lactide content (4.2 wt-% and 2.0 wt-%). Triclosan (TCS), ketoprofen (KTP) and p-coumaric acid (CUM) were selected as bactericide, antiinflammatory and antioxidant agents, respectively. Single, binary and ternary drugloaded microfibers having a unimodal diameter distribution could be prepared using a common chloroform:acetone:dimethylsulfoxide mixture and similar operational parameters (i.e. voltage, flow rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Incorporation of drugs into electrospun scaffolds is also an easy process since only minor modifications on the processing parameters are required, being also minimal the repercussion on the final geometry due to the usually low amount of loaded drug that is necessary to get a significant pharmacologic effect. Incorporation of several drugs can provide materials with multifunctional properties . In this work the use of a typical bactericide agent (i.e., polyhexamethylene biguanide (PHMB)) and an anticancerigen drug (i.e., curcumin (CUR)), which in addition has a bacteriostatic effect, was assayed in order to provide a high added value to the new scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of drugs into electrospun scaffolds is also an easy process since only minor modifications on the processing parameters are required, being also minimal the repercussion on the final geometry due to the usually low amount of loaded drug that is necessary to get a significant pharmacologic effect. Incorporation of several drugs can provide materials with multifunctional properties . In this work the use of a typical bactericide agent (i.e., polyhexamethylene biguanide (PHMB)) and an anticancerigen drug (i.e., curcumin (CUR)), which in addition has a bacteriostatic effect, was assayed in order to provide a high added value to the new scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of several drugs can provide materials with multi functional properties. [22] In this work the use of a typical bactericide agent (i.e., polyhexamethylene biguanide (PHMB)) and an anticancerigen drug (i.e., curcumin (CUR)), which in addition has a bacteriostatic effect, was assayed in order to provide a high added value to the new scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…For all these cases, the predicted drug delivery devices resulted in complete release within the specified time durations. Polybutylene succinate and polyvinyl alcohol-based controlled delivery devices are also reported in the open literature that show rapid release in several studies (Li, Wang, & Wu, 1998;Llorens, Ibañez, Del Valle, & Puiggalí, 2015;Shah, Shah, & Pradhan, 1997). It was observed for Case 2 that Paclitaxel was released from polylactic acid in monolithic cylindrical diffusion-controlled drug delivery device of radius 50 nm with initial drug loading of 7.5% (w/w) for 29 days with an optimal AUC of 63.60 × 10 3 ng.day/ml using 122 × 10 7 nanoparticles.…”
Section: Optimization Resultsmentioning
confidence: 97%
“…However, the T g remained unaltered, which confirmed that there was no interaction between OFLX and PLLA in the amorphous region. The antibiotic drug disrupts the polymer crystallization, thereby reducing the thermal stability. DSC curves for the PLLA nanofibrous mats with various formulations are shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%